Imagining by feeling: a case for compassion in legal reasoning. Issue 2 (12th May 2017) - Del Mar, Maksymilian
Abstract: This paper argues that feeling compassion (and other relational emotions) makes an important, beneficial difference in adjudication, as it improves the exercise of the perspectival imagination – that is, it helps a judge to better understand, and to better describe, a situation as another person experienced it. Even where a judge has a highly developed capacity for empathy and sympathy (these being cognitive and evaluative processes that are distinguishable from emotions), there is something to be gained by a judge actually feeling compassion. However, given the potential for the distortion of understanding as a consequence of feeling compassion, any such feeling has to be accompanied by the robust exercise of the perspectival imagination – that is, by imagining multiple perspectives (including sometimes constructing imaginary ones), so as to avoid privileging any one perspective over others. It is further argued that this 'imagining by feeling', as I call it in this paper, is not a threat to impartiality or the rule of law, but in fact a condition of it. It is part of the rule of law that people have a right to be heard, especially those whom we may otherwise find it difficult to understand. Imagining by feeling helps judges to better 'hear' a greater diversity of those who come before them, and thus helps the judiciary to improve the quality of the rule of law.